Finite Element Approach for Simulation of Powder Mixed Electric Discharge Machining Process and Experimental Validation - Singh, Kulwinder (My University, 2011)
Electrical Discharge Machining (EDM) is one of the most extensively used nontraditional material removal process capable of machining tough, high strength, corrosion resistant electrically conductive materials. Mixing of suitable material in powder form into the dielectric fluid is a recent advancement in EDM process to improve its process capabilities and is known as powder mixed EDM (PMEDM) process. Present work aimed at studying the thermal aspects of Powder Mixed EDM process using ANSYS Workbench 12.0 (Transient Thermal Analysis module and Static Structural Analysis module) to simulate temperature distribution, volume removed, cooling rate and stresses developed into the workpiece. Study is related to temperature distribution due to a single spark for one cycle varying different process parameters employing the Gaussian type of heat distribution inside the spark channel. Temperature distribution simulated using Transient Thermal analysis module is used to estimate volume removed and temperature variation in radial and depth direction using a code developed with Visual C++ 6.0. Development of different temperature zones (unaffected, heat affected, melting and evaporating zone), shape and size of the craters have been studied. Temperature distribution during simulation is found to be maximum at centre of spark region and decrease in radial direction following Gaussian distribution. Cooling rate of the workpiece material have been estimated using different discharge current, fraction of heat incident, pulse on and pulse off duration for a one complete cycle. Coupled Thermal-Structural analysis has been done to find stresses that develop into work material during PMEDM process. For validation experiments have been conducted on the H11 (hot die steel) workpiece using different set of process parameters. Experimental validation confirmed that 20 to 25% heat is transferring to the workpiece as predicted volume using Cw ranging from 0.2 to 0.25 during simulation is found to match with experimental volume removed for different pulse on and discharge current settings. Observing microstructure cracks appearing on the machined surface validates higher cooling rate and equivalent stresses predicted during simulation. Detailed study of the craters using microscope was completed to confirm the shapes and sizes of the craters that formed during the experimentation.
M.E. (CAD/CAM and Robotics)
Keywords: Power mixed EDM; Simmulation; Experimental validation